2021
DOI: 10.1093/femsec/fiab164
|View full text |Cite
|
Sign up to set email alerts
|

Transmission studies and the composition of prokaryotic communities associated with healthy and diseasedAplysina cauliformissponges suggest thatAplysinaRed Band Syndrome is a prokaryotic polymicrobial disease

Abstract: Aplysina cauliformis, the Caribbean purple rope sponge, is commonly affected by Aplysina Red Band Syndrome. This transmissible disease manifests as circular lesions with red margins and results in bare spongin fibers. Leptolyngbya spp. appear to be responsible for the characteristic red coloration but transmission studies with a sponge-derived isolate failed to establish disease, leaving the etiology of ARBS unknown. To investigate the cause of ARBS, contact transmission experiments were performed between heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 130 publications
0
1
0
Order By: Relevance
“…Chaib De Mares et al ( 2018 ) previously showed that close relatives of Pseudohongiella were among the most metabolically active bacterial associates of A. aerophoba . Monti et al ( 2021 ), furthermore, observed them to be enriched in diseased tissue of A. cauliformis . Moreover, and in accordance with their specific proliferation in heat-treated microcosms, Pseudohongiella strains isolated from seawater grew optimally at a temperature of 30°C (Xu et al 2016 ).…”
Section: Discussionmentioning
confidence: 98%
“…Chaib De Mares et al ( 2018 ) previously showed that close relatives of Pseudohongiella were among the most metabolically active bacterial associates of A. aerophoba . Monti et al ( 2021 ), furthermore, observed them to be enriched in diseased tissue of A. cauliformis . Moreover, and in accordance with their specific proliferation in heat-treated microcosms, Pseudohongiella strains isolated from seawater grew optimally at a temperature of 30°C (Xu et al 2016 ).…”
Section: Discussionmentioning
confidence: 98%